Revised Guidelines for Foreign Exchange Reserve Management. (Policy Papers; Policy Paper, 2013)
The 2013 revision of the Guidelines was carried out by the IMF staff, supported by a small Working Group of central banks and monetary authorities from China, India, Israel, Italy, Mexico, Japan, Russia, Saudi Arabia, Switzerland, the European Central Bank, and the Bank for International Settlements, and The World Bank acting as reviewer in the process. Mr. Franco Passacantando, Managing Director at the Bank of Italy, chaired this Working Group. The revisions to the Guidelines mainly concentrate on: (i) reserve management objectives and strategy, including analyzing and managing risks in the context of reserve diversification; (ii) transparency and accountability, while avoiding reserve management decisions being dictated by the prevailing accounting framework; (iii) institutional and organizational framework issues, especially on avoiding possible inconsistencies between reserve management and other central bank operations; and (iv) the risk management framework, including taking into account ex-ante assessments of the impact of reserve investments on financial markets and building internal credit risk assessment systems to assess counterparty risks.